1996
DOI: 10.1126/science.271.5247.342
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Monomeric 23-Residue Polypeptide with Defined Tertiary Structure

Abstract: Small proteins or protein domains generally require disulfide bridges or metal sites for their stabilization. Here it is shown that the beta beta alpha architecture of zinc fingers can be reproduced in a 23-residue polypeptide in the absence of metal ions. The sequence was obtained through an iterative design process. A key feature of the final design is the incorporation of a type II' beta turn to aid in beta-hairpin formation. Nuclear magnetic resonance analysis reveals that the alpha helix and beta hairpin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
216
0
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(229 citation statements)
references
References 33 publications
7
216
0
6
Order By: Relevance
“…From both CD and NMR data, @pep-3, which contains the tight-turn-forming sequence YDWKV (Varnum et al, 1993), is observed to induce a greater population of @-sheet than found in @pep-2. This apparent turn-induced increase in conformational stability also has been observed in a designed 23-residue +peptide simply by shifting from a type-I1 to type-11' @-turn motif (Struthers et al, 1996). There, however, aggregation apparently was not inducing folding.…”
Section: K H Muyo Et Ulsupporting
confidence: 62%
“…From both CD and NMR data, @pep-3, which contains the tight-turn-forming sequence YDWKV (Varnum et al, 1993), is observed to induce a greater population of @-sheet than found in @pep-2. This apparent turn-induced increase in conformational stability also has been observed in a designed 23-residue +peptide simply by shifting from a type-I1 to type-11' @-turn motif (Struthers et al, 1996). There, however, aggregation apparently was not inducing folding.…”
Section: K H Muyo Et Ulsupporting
confidence: 62%
“…Unfortunately, initial attempts to design proteins led to structures that formed molten globulelike states with dynamic behavior relative to natural proteins. More recently, it has been possible to design small uniquely folded proteins that incorporate all of the commonly occurring secondary structural and supersecondary structural motifs (29)(30)(31)(32)(33)(34)(35)(36). These studies illustrated the delicate interplay of forces that define the uniquely folded structures of proteins; hydrophobicity provides a strong driving force for folding, but designs based on this consideration alone often adopt dynamically averaging Abbreviations: DF1, Due Ferro 1; PDB, Protein Data Bank.…”
mentioning
confidence: 99%
“…There has been wide spread use of this simple design strategy as a method for rational design of b-hairpin folds (Dhanasekaran et al 1999;Mohanraja et al 2003). Imperiali and coworkers used this device beneficially for rational design of a small and synthetic protein called BBA (Struthers et al 1996) (Fig. 6).…”
Section: De Novo Design Of Hetero-chiral Proteinsmentioning
confidence: 99%
“…Ghadiris nanotube's and gramicidin-A perhaps best exemplify the prospect (Ghadiri et al 1994;Urry 1971;Wallace 2000). Likewise several reported hairpin peptides and mini-proteins directed or stabilized by one or more D chiral residues are examples of downsizing achieved by de novo design (Dhanasekaran et al 1999;Durani 2008;Struthers et al 1996). Possibly the first known heterochiral fold of complex sequence chirality was a hexapeptide reported by Fabiola et al (1997).…”
Section: De Novo Design Of Hetero-chiral Proteinsmentioning
confidence: 99%